Financial innovation and sustainability: Green, blue and sustainable finance - Ziolo, Magdalena; Zaleska, Malgorzata (London Routledge, 2025)
This book focuses on the intersection between nature and finance and offers a comprehensive overview of the trends, transformations and challenges in finance and the financial markets related to the effects of sustainability concepts or ESG factors. The book has been designed to show these trends, through the evolving subdisciplines of finance, such as green and blue finance.